TOWARDS THE WHOLE-SCHOOL APPROACH: THE CHANGING NATURE OF “BEST PRACTICE” FOR REFUGEE EDUCATION IN AUSTRALIA - Harrison James Spratling (International Journal of Educational Best Practices, 2022)
Since 2000, the dynamics and demographics of refugee education in Australia have changed constantly. Meanwhile, academic literature on refugee education continues to explore best practice approaches in various contexts. While these realities continue to shift, it is important to analyze any changes in what Australian literature considers best practice for refugee education. To analyze such changes, this study conducts a qualitative content analysis of academic literature published in Australia since 2000 and draws out various themes of best practice. It then analyses studies chronologically to detect change in the concept of best practice for holistic refugee education over time. The goal of holistic education is suitable for refugee students who often have extremely complex learning needs, and as such it forms the basis for what this study considers “best practice” education should strive to achieve. This study reveals that current best practice for supporting refugee students in Australia includes whole-school approaches to inclusivity, study and mental health supports, and community and family engagement. Additionally, professional training and appropriate pedagogical approaches, especially relating to literacy and supplemented by adequate resources, are vital to successful refugee education. It also reveals that since 2012, academic literature has places more emphasis on staff professional development, inclusivity, advocacy and the positive framing of refugees, and the whole-school approach to refugee education, whilst placing less emphasis on links between schools, families and refugee communities, as well as mental health and study supports for refugee students. Literature on the importance of pedagogy has remained constant since 2000.